Progress and Challenges in Fracture Prediction of Die-Cast Lightweight Alloys - Liu, Kaiyue (International Journal of Materials Science and Technology Studies, 2025)
Die-cast alloys, such as aluminum, zinc, and magnesium alloys, are widely used in automotive, aerospace, and consumer electronics applications due to their excellent mechanical properties, castability, and cost-effectiveness. Fracture failure, however, remains a critical concern, directly affecting performance and service life. This review summarizes current advances in fracture prediction for die-cast alloys, including common alloy types, fracture mechanisms, failure modes, influencing factors, and predictive models. Key studies are cited to highlight the coupled effects of microstructural defects, stress state, and temperature on fracture behavior, and the applicability and limitations of models such as GISSMO and MMC are discussed. Future research directions are also outlined.